Clinical care of the runner. Assessment, biomechanical principles, and injury management (Elsevier, 2020)
Offering current guidance from national and international experts, Clinical Care of the Runner provides a comprehensive, practical approach to caring for the runner patient. Editor Dr. Mark A. Harrast, Clinical Professor of Rehabilitation Medicine and Sports Medicine and Medical Director for Husky Stadium and the Seattle Marathon, ensures that you`re up to date with assessment, biomechanics, musculoskeletal injuries, medical illness, training, special populations, and other key topics.